O sytuacji językowo-kulturowej Truskolas i wsi okolicznych w gminie Wręczyca Wielka w XXI w. .......... 625 - Jelonek, Tomasz (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
ON THE LINGUISTIC-CULTURAL SITUATION OF TRUSKOLASY AND THE NEIGHBOURING VILLAGES IN THE WRĘCZYCA WIELKA COMMUNITY IN THE 21ST CENTURYThe article attempts to outline the contemporary linguistic and cultural situation of Truskolasy and the neighbouring villages in the Wręczyca Wielka community near Kłobuck in the north of the Silesian province of Poland. The linguistic material consists of informal utterances from the middle and older generations, continuously collected by this author since 2011 during informal conversations with the locals. The analysis also utilizes information obtained from employees of cultural and educational institutions and members of local organisations. The analytic part of the article contains, among others, an overview of the characteristics of contemporary spoken Polish of the residents of Truskolasy and the neighbouring villages. Moreover, the paper highlights selected elements of the region’s culture.